Antara Paradigma dan Kritik: Studi Makki-Madani dalam Perspektif Mahmud Muhammad Thaha dan Nasr Hamid Abu Zayd - Baehaki, Ahmad; Siti Nurkholisoh (ABHATS: Jurnal Islam Ulil Albab, 2026)
The traditional study of Makki–Madani has been classified by classical scholars based on the place of revelation, the time of revelation, and the target audience of the verses. This understanding is closely related to the theory of naskh–mansūkh, in which the Madaniyyah verses are considered to abrogate the Makkiyyah verses. However, this classical approach has been criticized by modern thinkers such as Mahmud Muhammad Thaha and Nasr Hamid Abu Zayd, who offered alternative paradigms. This article aims to examine the views of these two figures in order to assess their relevance to contemporary Qur’anic studies. Using a library research method and employing classical Makki–Madani theory along with the classical theory of naskh as analytical frameworks, this study finds that Thaha interprets Makki–Madani through the criterion of the addressee (khitāb) and emphasizes the occurrence of reciprocal naskh between the two. Meanwhile, Abu Zayd proposes a new classification that highlights the dialectic between reality and text: reality as a dynamic historical context, and text as content and linguistic structure. Unlike Thaha, Abu Zayd rejects the simplification of the naskh–mansūkh relationship based solely on the Makki–Madani dichotomy without taking into account the historical context of asbāb al-nuzūl and the chronology of revelation. These findings demonstrate that a re-reading of the Makki–Madani category is necessary, not only to critique classical approaches but also to enrich contemporary Qur’anic discourse with more contextual and critical perspectives. [Kajian Makki–Madani secara tradisional diklasifikasikan oleh ulama klasik berdasarkan tempat turunnya, waktu pewahyuan, dan objek sasaran ayat. Pemahaman ini erat kaitannya dengan teori naskh–mansūkh, di mana ayat-ayat Madaniyyah dipandang menasakh ayat-ayat Makkiyyah. Namun, pendekatan klasik tersebut mendapat kritik dari pemikir modern seperti Mahmud Muhammad Thaha dan Nasr Hamid Abu Zayd yang menawarkan paradigma alternatif. Artikel ini bertujuan mengkaji pandangan kedua tokoh tersebut guna menilai relevansinya bagi studi Al-Qur’an kontemporer. Dengan metode kajian pustaka dan menggunakan teori Makki–Madani klasik serta teori naskh klasik sebagai kerangka analisis, penelitian ini menemukan bahwa Thaha menafsirkan Makki–Madani melalui klasifikasi objek sasaran (khitāb) serta menekankan adanya perputaran naskh antara keduanya. Sementara itu, Abu Zayd mengusulkan klasifikasi baru yang menekankan dialektika realitas dan teks: realitas sebagai konteks historis yang dinamis, dan teks sebagai kandungan isi serta struktur linguistik. Berbeda dengan Thaha, Abu Zayd menolak penyederhanaan relasi naskh–mansūkh berdasarkan dikotomi Makki–Madani semata tanpa memperhitungkan konteks historis asbāb al-nuzūl dan kronologi pewahyuan. Temuan ini menunjukkan bahwa pembacaan ulang terhadap kategori Makki–Madani diperlukan, tidak hanya untuk mengkritisi pendekatan klasik, tetapi juga untuk memperkaya wacana tafsir kontemporer dengan perspektif yang lebih kontekstual dan kritis.]